On Certain Issues of Testamentary Inheritance in Serbian Law – de lege ferenda (Part II) - Vidić , Jelena; Kovacevic, Milica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
For the valid creation of a will as a legal transaction mortis causa, a necessary condition is to be expressed in one of the legally recognized forms. The requirement of form dates back to Roman law, where formal prerequisites were given different functions. The article tries to determine whether and in what way the formal requirements of certain will types can be adapted to the development of information technologies, while examining the positive legal regulations. Analyzing the existing legislative activity focused on wills drawn up in electronic form and the current opinions in the doctrine, the authors try to assess whether in Serbian law will in whose composition some type of electronic medium was used, could produce legal effects according to the current rules, as well as to propose de lege ferenda solutions on the legislative level in that direction.